ESENSI KAIDAH TIKRARIYAH DALAM MEMAHAMI BAHASA ARAB - Bambang Hermanto; Anwar Rudi (Institut Kariman Wirayudha Sumenep, 2022)
Students, low level of understanding in Arabic learning can be influenced by several factors, such as the lack of mastery of Arabic vocabulary because to determine the level of understanding of students one of them can be measured by achievement or learning outcomes. Other factors, like a teacher’s lack of enthusiasm in applying methods. Teachers tend to use the lecture method, thus making students bored, sleepy and the class tends to lose concentration. The tikrar method is a form of the old method but is still relevant and widely used today. This method is an answer and a solution in the midst of the vacuum of Arabic teachers when they do not find the best solution in Arabic classes. This method is a unique learning method because it focuses on the learner to be able to master this technique. Because there is a direct learning process there using a variety of techniques. To overcome the existing problems, it is necessary to improve the use of fun ways in the learning process. By applying the tikrar method or the takririyah method, the author believes that he will be able to provide convenience in mastering and memorizing Arabic vocabulary.